2023
DOI: 10.1088/2515-7655/acbb2a
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt nickel boride as electrocatalyst for the oxidation of alcohols in alkaline media

Abstract: A mixed Co and Ni boride precursor was synthesized via chemical reduction and subsequently annealed at 400 or 500 °C with or without prior addition of the monomer benzoxazine. The resulting mixed CoNiB materials were investigated as electrocatalysts for three alcohol oxidation reactions (AOR) in alkaline electrolyte: the oxidation of glycerol (GOR), ethylene glycol (EGOR) and ethanol (EOR). Comparison of the rotating disk electrode (RDE) cyclic voltammograms for the different catalysts revealed that CoNiB anne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…[4] Many researchers are currently investigating suitable catalyst materials, [5] and their intrinsic properties such as activity and stability during the oxygen evolution reaction (OER). [6] However, these intrinsic properties do not stand independently, but are superimposed on extrinsic properties such as morphology, adhesion, cohesion, and transport capabilities. [7] The interrelation between these properties poses an ongoing challenge, and AWE anodes have not yet reached their potential operational thresholds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Many researchers are currently investigating suitable catalyst materials, [5] and their intrinsic properties such as activity and stability during the oxygen evolution reaction (OER). [6] However, these intrinsic properties do not stand independently, but are superimposed on extrinsic properties such as morphology, adhesion, cohesion, and transport capabilities. [7] The interrelation between these properties poses an ongoing challenge, and AWE anodes have not yet reached their potential operational thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…The application of AWE allows the inclusion of non‐precious metals as electrocatalysts, thus creating a broader scope for the discovery of new catalysts [4] . Many researchers are currently investigating suitable catalyst materials, [5] and their intrinsic properties such as activity and stability during the oxygen evolution reaction (OER) [6] . However, these intrinsic properties do not stand independently, but are superimposed on extrinsic properties such as morphology, adhesion, cohesion, and transport capabilities [7] .…”
Section: Introductionmentioning
confidence: 99%
“…The pool of applicable AOR catalysts can be divided into two groups, with both having their own advantages and disadvantages. The first is the nonnoble metal catalysts based on, for example, Co, Ni, etc. The common feature of these materials is that the onset potential of the AOR is above the oxidation potential of the catalyst surface (≈+1.10 V RHE ); hence, AOR is most likely driven by radicals, just as in the case of the OER.…”
Section: Introductionmentioning
confidence: 99%
“…1 Several non-precious metals, including Sn, Bi, and Ni, have been investigated for their performance in ethanol electrooxidation. However, to address their limited catalytic properties and stability, these metals need to be combined with other metals, such as PtSn, 2 PtSnRh, 3 PtBi, 4 RhBi, 5 PdPtNi, 6 CoNiB, 7 CoNi, 8 to improve their low catalytic properties and stability. Previous studies identified Platinum 9–11 and Palladium 12 as the efficient electrocatalysts for low-temperature DEFC applications.…”
Section: Introductionmentioning
confidence: 99%